2007
DOI: 10.1007/s11325-006-0095-5
|View full text |Cite
|
Sign up to set email alerts
|

Association of physical activity with sleep-disordered breathing

Abstract: This study was performed to determine whether there is a protective association between participation in vigorous or vigorous/moderately vigorous physical activity and the prevalence of sleep-disordered breathing (SDB). Polysomnographic and questionnaire data from the baseline examination of 4,275 participants in the Sleep Heart Health Study (SHHS) were analyzed in relation to information on amount of physical activity and other potentially relevant factors collected from five SHHS parent cohorts (Atherosclero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
81
2
7

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(99 citation statements)
references
References 33 publications
6
81
2
7
Order By: Relevance
“…Consistent with the findings of this study, previous large community-based samples have reported an association between exercise and reduced risk of OSA. In some of these previous findings, such an association did not persist after accounting for body habitus, 6,11 while in others an association remained.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…Consistent with the findings of this study, previous large community-based samples have reported an association between exercise and reduced risk of OSA. In some of these previous findings, such an association did not persist after accounting for body habitus, 6,11 while in others an association remained.…”
Section: Discussionmentioning
confidence: 83%
“…11 However, unlike the Sleep Heart Health Study, 23 the present study examined occupational activity and exercise, employed a single validated exercise activity questionnaire, and had a larger OSA group. As a result, the present study was able to define nil and low exercise categories.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Literatürde yer alan çal malarda ya , vücut kitle indeksi, fiziksel aktivite al kanl ve e itim durumunun solunum fonksiyonlar n , egzersiz kapasitesini ve ya am kalitesi düzeyini etkileyebilece i bildirilmektedir [14][15][16]. Bu nedenle; sosyodemografik özellikler ve hava yolu obstrüksiyon iddetini gösteren FEV 1 de eri aç s ndan çal -maya dahil etti imiz her iki hastal k grubundaki hastalar n benzer özelliklere sahip olmas n n verilerin kar la t rmas nda kolayl k sa lad dü ünülmektedir.…”
Section: Tarti Maunclassified